2005
DOI: 10.1080/j354v19n04_07
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Arthritis Pain Management with Topical Morphine

Abstract: Chronic pain is a major health problem in the United States affecting 50 to 75 million Americans. The extent of pain encountered with chronic disease states may impact an individual's quality of life. Morphine is the drug of choice for severe pain. The primary purpose of the study was to determine analgesic response with the use of topical morphine to control chronic pain in a series of patients with arthritis pain. The second purpose was to detect the presence of morphine in the urine following topical admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Although data regarding topical gel formulations of opioids is sparse, studies of topical morphine [125–127] and hydromorphone [128] have been published. Oxymorphone was tested on human skin and was found to have permeability rates that were “low unless skin permeation enhancers were included in the vehicle” [8,129].…”
Section: Resultsmentioning
confidence: 99%
“…Although data regarding topical gel formulations of opioids is sparse, studies of topical morphine [125–127] and hydromorphone [128] have been published. Oxymorphone was tested on human skin and was found to have permeability rates that were “low unless skin permeation enhancers were included in the vehicle” [8,129].…”
Section: Resultsmentioning
confidence: 99%
“…A recently published case series reported the potential bene fi t of "topical" morphine in the management of chronic osteoarthritis-related pain; however, since the report emphasized that morphine or its metabolites were identi fi able in the urine of treated patients, it is unclear how truly "topical" this preparation was [ 90 ] .…”
Section: Nsaidsmentioning
confidence: 98%
“…In this study, the authors detected the presence of morphine (31-191 ng/mL) in the urine of three arthritis patients over time, suggesting possible contribution of systemically absorbed morphine to the observed analgesic effect. 44 More recently, Ciałkowska-Rysz et al found self-administered topical morphine to be a highly effective and safe medication for treating mucosal and skin lesions in palliative cancer patients, providing sustained pain relief for over 28 days. 41 The studies discussed above also suggest that the transdermal route is associated with a higher patient compliance as it offers evasive dosing, the possibility of self-administration, and flexibility in adjusting dosing regimen to experience rapid and long-lasting pain relief, hence the interest in accurate modeling and simulation.…”
Section: Dovepressmentioning
confidence: 99%